Islamic Parenting Model in Character Building of Santri at Nurul Jadid Islamic Boarding School - Arifin, Misbahul; Sholeha, Fina Wildania; Ahmad, Amala Bilqis (STKIP Pesisir Selatan, 2025)
This study focuses on the Islamic parenting model as a strategy for character formation among students at Nurul Jadid Islamic Boarding School, aiming to reveal how the habituation of worship, the internalization of the santri trilogy, and social regulation contribute to shaping discipline, responsibility, and moral awareness amidst the challenges of the digital era. The research employed a qualitative approach with a case study method, conducted at Nurul Jadid Islamic Boarding School, KH. Zaini Mun’im Street, Karanganyar, Paiton, Probolinggo, East Java, in August 2025. Data were collected through in-depth interviews with administrators, teachers, and students, complemented by field observations and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the Islamic parenting model functions not only as a set of rules but also as an integral strategy that fosters spiritual discipline, social solidarity, and students’ self-control. The santri trilogy proved to be a foundational value that strengthens character development through habituation and role modeling, while the regulation of gadget use serves as an adaptive solution to the challenges of digitalization. This study highlights that Islamic Boarding School serve as effective social laboratories in nurturing the moral consciousness of younger generations. The implication is that the Islamic parenting model can be developed as an alternative framework for character education that is relevant to Islamic educational institutions in addressing the moral crisis in the era of globalization.